Automatic categorization of book collections / N. Idris and A. Dennis - Idris, N.; Dennis, A. (2002)
Automatic text categorization is an important research area and has a potential for many text-based applications. This paper discussed the role of the information retrieval (IR) as a way of categorizing books automatically called Smart Database Assistant. It is a system for accessing and categorizing collections of books, which involved two modules, the Public User Module and the Administrator Module. These two modules offer an approach to accessing and categorizing text-based books collections by the keywords of the contents or themes that are described by a user which based on the indexing process. To test the effectiveness of the developed system, an experiment was conducted against a number of books from different category. The result showed that the information retrieval offers an acceptable performance where it is applicable for categorizing the book collections.